Respuesta :
Step-by-step explanation:
Solution,
According to BODMAS(Bracket of multiplication, division, addition and subtraction),
- 2×1+52-36÷2
- 2×1+52-18
- 2+52-18
- 54-18
- 36
Answer:
Solution :
To solve the above equation we will follow the BODMAS rule.
- >> BODMAS is an order of mathematic operations.
- >> BODMAS rule is to be followed while solving expressions in mathematics.
It stands for :
[tex]\quad\begin{gathered} \small \begin{array}{l} \star \: \rm B= bracket \\\star \: \rm O= order \: of \: power \: \\\star \: \rm D= division \\\star \: \rm M= multiplication \\ \star \: \rm A= addition \\ \star \: \rm S=subtraction \end{array}\end{gathered}[/tex]
Solving the question by bodmas rule :
[tex] \tt{ = 2 \times 1 + 52 - 36 \div 2}[/tex]
[tex] \tt{ = 2 \times 1 + 52 - \dfrac{36}{2}}[/tex]
[tex] \tt{ = 2 \times 1 + 52 - \cancel{\dfrac{36}{2}}}[/tex]
[tex] \tt{ = 2 \times 1 + 52 - 18}[/tex]
[tex] \tt{ = 2 + 52 - 18}[/tex]
[tex] \tt{ = 54 - 18}[/tex]
[tex] \tt{ = {\underline{\underline{\red{ \: 36 \: }}}}}[/tex]
Hence, the answer is 36.